2015
DOI: 10.1183/09031936.00011415
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between asthma and suicidal behaviours: a systematic literature review

Abstract: Asthma is a highly prevalent chronic condition worldwide, and is particularly common in younger people compared to other chronic conditions. Asthma can result in a number of symptoms that are detrimental to the quality of life of sufferers. The aim of the present systematic literature review was to analyse the existing literature on the relationship between asthma and fatal and nonfatal suicidal behaviours.Articles were retrieved from Scopus, PubMed, ProQuest and Web of Knowledge. We searched for the terms (su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…7 In addition to these adverse physical and social impacts, a number of studies consistently linked atopy to poor psychological outcomes, including major depression 8,9 and anxiety. 10 A recent systematic review presented a link between asthma and suicidal behaviors 11 ; however, there are no current systematic reviews on the possible association between allergies and suicidal behaviors. Hence, the aim of the current article was to conduct a systematic literature review to explore the potential link between allergies and fatal and nonfatal suicidal behaviors.…”
mentioning
confidence: 99%
“…7 In addition to these adverse physical and social impacts, a number of studies consistently linked atopy to poor psychological outcomes, including major depression 8,9 and anxiety. 10 A recent systematic review presented a link between asthma and suicidal behaviors 11 ; however, there are no current systematic reviews on the possible association between allergies and suicidal behaviors. Hence, the aim of the current article was to conduct a systematic literature review to explore the potential link between allergies and fatal and nonfatal suicidal behaviors.…”
mentioning
confidence: 99%
“…Ultimately, many pollen particles are too large to deposit in the lungs, although certain pollens, such as rye-grass pollen have demonstrated the ability to induce asthmatic effects similar to air pollutants. This is of relevance because asthma has shown positive associations with suicidal behaviors (115,116). Interestingly it has been demonstrated that in contrast to air pollutants, nonallergic asthma has been associated with higher levels of CRP than allergic asthma (117).…”
Section: Aeroallergensmentioning
confidence: 99%
“…Oxidative stress, which has been hypothesized as a mediator of prenatal stress and atopic dermatitis, could be another possible candidate . Apart from such possible underlying pathways, a direct causal relationship, unmeasured confounders, or common genetic link may also explain this association . Another potential cause of suicidal ideation in asthmatic adolescents is the use of corticosteroids, which may induce adverse psychiatric symptoms .…”
Section: Introductionmentioning
confidence: 99%